633 Surveillance for Head and Neck Cancer Recurrences: Is There Scope for A Tailored Approach?. (4th May 2021) - Alvi, M; Eagles, E; Hamilton, D
Abstract: Introduction: Detection of cancer recurrence after treatment of head and neck cancer (HaNC) is vital. Current guidelines stipulate that following primary treatment HaNC patients are followed up for five years with a total of 18-24 appointments. This forms a bulk of the HaNC surgeon's workload. Asymptomatic recurrences are rare. Patients educated regarding worrying symptoms may institute their own follow up. Such open appointment systems may be as effective at detecting recurrences Method: At a moderate volume HaNC centre we reviewed 98 patients that had completed their five year follow up. We investigated cancer recurrences and whether these were symptomatic or asymptomatic at time of detection. We analysed each recurrence regarding the time since primary treatment. Results: 23 patients had HaNC recurrences. These recurrences were symptomatic in 17 patients and asymptomatic in 6 patients. Five of the six patients from the asymptomatic group had recurrences within two years of primary treatment. The final patient was of a high-risk histological subtype. Conclusions: Asymptomatic cancer recurrences are uncommon especially after two years of regular follow up. After two years the frequency of appointments may be tailored on a patient-by-patient basis. Patients educated regarding symptoms of cancer recurrences may institute their own follow up.